Resolvemos problemas con valor absoluto dirigido a estudiantes de segundo grado de educación secundaria - Saavedra Díaz, Jorge Felipe Andrés (2022)
Through the present work of professionalsufficiency called "We solve problems with absolute value directed to students of second grade of Secondary Education" has as purpose that in the educational institution Rafael Narvaez Cadenillas, the students have a clear concept about the absolute value and its correct use in the different problems that are presented to us; through the use of digital tools and through a systematic process established in a learning session, giving response to the pedagogical processes to develop the mathematical competences and to fulfill the demands of the case. The didactic and pedagogical principles and models, support the learning session, as one of the ways to meet the needs of students based on the process of teaching mathematics to achieve meaningful, functional and formative learning, taking problem solving as the basis for developing the thematic field of mathematics, attending to Approach of the area developing transversal competencies: Management of the Autonomous Learnings and Management of Technologies.